Promoting active reading comprehension strategies: A resource book for teachers - Judith Westphal Irwin (Prentice-Hall, 1989)
This book is intended for both remedial reading teachers and classroom teachers. It contains activities for all ages and ability levels. Though it contains the most current and exciting new approaches, it requires no extra training beyond that given to teachers who already teach in some way